Frequency of Type 2 Diabetes mellitus and Impaired Glycemia in a Teaching Hospital of South-Western Nepal - Pokharel, DR; Gautam, N; Archana, J; Nagamma, T; Kumar, R; Sapkota, R M (Asian Journal of Medical Sciences, 2012)
Objective: The aim of this study was to determine the frequency of type 2 diabetes, impaired fasting glucose (IFG) and impaired glucose tolerance (IGT) among patients visiting a tertiary level teaching hospital in south-western Nepal. Material & Methods: This is a retrospective study conducted among subjects (n=17082) who visited outpatient department of the Universal College of Medical Sciences Teaching Hospital (UCMSTH), Bhairahawa, Nepal for their medical checkup. Data related to age, sex, hospital number and blood glucose concentration of the study subjects were collected from hospital records and analyzed for the frequency study. Results: The average frequency of type 2 diabetes was found to be 6.1% over a period of five years and it was significantly (p=0.0232) higher in males (3.4%) than in females (2.8%). Frequency of IFG and IGT were found to be 2.31% and 2.70% respectively. The frequency of type 2 diabetes, IFG and IGT was significantly higher in males and age group of 51-60 years. Conclusion: The frequency of type 2 diabetes and impaired glycemia is increasing every year in south-western part of Nepal. We recommend that efforts be made by all the stakeholders to curb this emerging medical problem before it becomes epidemic in the general population. DOI: http://dx.doi.org/10.3126/ajms.v2i3.5485 Asian Journal of Medical Sciences 2 (2011) 202-206